AN ANALYSIS OF THE REFLECTIONS OF NEWS ABOUT SOCIAL INCIDENTS ON SOCIAL MEDIA - SÜTCÜ, CEM SEFA (ISTANBUL UNIV, 2016)
Social Media, which has become an integral part of the everyday life of individuals, is also influential on the news media. This development not only introduces new expansions to the field of communication but also changes the news habits. Furthermore, there are discussions about the accuracy of the news shared on Social Media and its reflection of reality. There is no comparative analysis of how news sharing on Social Media underwent change by year in the context of how news was delivered. How Social Media affects news source overtime is addressed in this research. The aim of the research is to comparatively reveal how participants' habits of news sharing on Social Media changed in the context of news sharing and news content in two different years. By this aspect, the study is distinguished from other similar So - cial Media studies. Quantitative research methods were applied in the research performed. Face-to-face surveys were made with a total of 2,348 university students in 2012 and 2013 by using the method of cluster sampling. The data was quantitatively subjected to statistical analyses. Within the scope of the research, the students only attached importance to the factor of 'news source' in 2012, whereas in the survey carried out in 2013, it was seen that 'news sharing' also turned out to be a significant factor be - sides the 'news source'. This finding demonstrates that people also increase the things they share while following mass events on Social Media
Keywords: News Source; News Content; News Sharing on Social Media; CREDIBILITY; INTERNET; PERCEPTIONS